Light sole material and preparation method thereof
By adding raw materials such as polyamide elastomer, thermoplastic polyurethane, hydrophobically modified nanocellulose aerogel and aramid fiber to the EVA resin material and cross-linking modification, the problem of EVA material hardening and increasing brittleness under low temperature environments is solved, and better flexibility, elasticity and thermal insulation effects are achieved.
Patent Information
- Application Number
- CN202411677724.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-01
AI Technical Summary
The molecular chain movement of EVA materials slows down in extremely cold environments, resulting in the sole material becoming hard, increasing brittleness, decreasing flexibility and elasticity, and prone to breaking or rupture.
EVA resin is used as the matrix and raw materials such as polyamide elastomer, thermoplastic polyurethane, hydrophobically modified nanocellulose aerogel and aramid fiber are incorporated to improve the cross-linking modification of the material through the action of cross-linking agent, form a fine cell structure, and enhance the tensile strength and elasticity of the material.
Maintain high flexibility and elasticity in low temperature environments, reduce the risk of brittle fracture, and improve the insulation effect and wear resistance of sole materials.
Smart Images

Figure BDA0005147450400000081 
Figure BDA0005147450400000091 
Figure BDA0005147450400000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and more specifically, to a lightweight sole material and a preparation method thereof. Background Art
[0002] Shoes are a necessity in people's daily life. With the development of science and technology and the improvement of people's living standards, people have higher and higher requirements for shoe quality and performance. According to literature reports, for every 100 grams of shoe weight increase, the wearer's physical energy consumption will increase by 1%. In order to reduce physical energy consumption and improve wearing comfort, lightweight foaming materials have become the main direction of research and development of sole materials. Compared with traditional solid sole materials, foaming sole materials have the advantages of light and comfortable wearing, excellent physical properties, and low cost, and have great development potential in the market of sports soles. The foaming sole with EVA (ethylene-vinyl acetate copolymer) as the matrix material has a smaller density and good plasticity, and because it has higher resilience and softness, it is more comfortable to wear and is favored by people.
[0003] In the prior art, a Chinese invention patent document with application number CN2014102118192 discloses a lightweight EVA sole material and a preparation method thereof. The material comprises the following components in parts by weight: 40-60 parts of EVA7350, 20-40 parts of lightweight silica filler, 5-15 parts of POE8003 colloid, 5-15 parts of industrial light powder, 1-5 parts of foaming agent, 0.2-0.6 parts of coupling agent, 0.5-1.5 parts of zinc oxide powder, and 0.3-0.7 parts of stearic acid. The lightweight sole material is obtained through the steps of internal mixing, open mixing, granulation, cooling, foaming, etc. The sole material effectively reduces the weight of the material itself, is lighter to wear, and has better comfort and elasticity.
[0004] However, EVA material has a high glass transition temperature. In extremely cold environments, the movement of molecular chains will slow down, causing the overall sole material to become harder, more brittle, and less flexible and elastic, making it more susceptible to breakage or cracking. Summary of the invention
[0005] In order to improve the flexibility of a lightweight EVA sole material in a low temperature environment, the present application provides a lightweight sole material and a preparation method thereof.
[0006] In a first aspect, the present application provides a lightweight sole material, which adopts the following technical solution: A lightweight sole material comprises the following raw materials, measured in parts by weight: 40-60 parts of EVA resin, 4-6 parts of polyamide elastomer, 8-12 parts of thermoplastic polyurethane, 8-24 parts of hydrophobically modified nanocellulose aerogel, 3-7 parts of aramid fiber, 1-3 parts of foaming agent, 1.5-2 parts of cross-linking agent, 20-40 parts of inorganic filler, 0.5-1.5 parts of zinc oxide and 0.3-0.7 parts of stearic acid.
[0007] By adopting the above technical scheme, EVA resin is used as the matrix, and raw materials such as polyamide elastomer, thermoplastic polyurethane, hydrophobically modified nanocellulose aerogel and aramid fiber are added. The polyamide elastomer is a new type of elastomer obtained by copolymerizing nylon hard segment and polyether or polyester soft segment, and has excellent wear resistance, high and low temperature resistance, tensile properties, antistatic properties and resilience. Under the action of a cross-linking agent, cross-linking modification is produced with the EVA resin. Moreover, the polyamide elastomer has a linear molecular chain structure, and an appropriate incompatible interface with the EVA resin is conducive to the formation of a fine pore structure. The internal pore structure of the foamed sole material system is improved, and when subjected to When external force acts, stress concentration can be avoided, thereby improving the tensile strength of the foamed sole material. In addition, the polyamide elastomer makes it easy to form bubble nuclei at the phase interface during the growth of the foam cells. The increase in the number of bubble nuclei can significantly reduce the apparent density of the sole material, and significantly improve the foaming ratio and resilience. In addition, the thermal conductivity of the polyamide elastomer is smaller, thereby significantly reducing the thermal conductivity of the foamed sole material. Moreover, the foaming system is a three-phase system, and bubble nuclei are formed at the phase interface. The foaming system has a smaller density and a higher ratio, thereby lowering the thermal conductivity, improving the thermal insulation effect of the sole material, preventing heat loss from footsteps, and having better warmth and heat preservation capabilities.
[0008] Thermoplastic polyurethane can enter between EVA molecular chains during hot melt flow to form tough support, destroy the brittle continuous structure, and then enhance the low-temperature toughness. Hydrophobically modified nanocellulose aerogel is mainly obtained by hydrophobically modifying nanocellulose. Nanocellulose is natural cellulose fiber obtained by physical treatment and chemical modification. It is a nanomaterial with high strength, high specific surface area and high surface energy. It is light and has good biocompatibility, but it has strong hydrophilicity and poor compatibility with matrices such as EVA resin. Therefore, it is hydrophobically modified to reduce its surface hydroxyl content, increase its hydrophobicity, improve dispersibility and compatibility, improve the tensile strength, tear strength and resilience of the sole material, and the thermal conductivity of the aerogel is extremely low, which can reduce Heat transfer, thereby maintaining more foot heat at low temperatures, achieving better thermal insulation effect, and reducing the hardening and embrittlement of the sole material under low temperature conditions; aramid fiber is a high-performance synthetic fiber with excellent mechanical properties and chemical stability, outstanding low-temperature resistance, and can still maintain excellent physical and chemical properties at a low temperature of -196°C. Under low temperature conditions, the tensile strength, modulus and wear resistance of aramid fiber remain stable, and there will be no obvious performance degradation due to temperature reduction. Therefore, it can improve the structural strength and low-temperature toughness of the foamed sole material, and aramid fiber is tough and can absorb a lot of energy. When impacted by external force, it can effectively disperse and absorb energy, reducing the risk of brittle fracture of the material at low temperatures.
[0009] Optionally, the method for preparing the hydrophobically modified nanocellulose aerogel comprises the following steps: The nanocellulose is dispersed in deionized water to prepare a suspension with a concentration of 1-1.5 wt%, and freeze-dried to obtain a nanocellulose aerogel; The lignin microspheres and lignin micro-nanospheres are mixed in a mass ratio of 1:0.5-1, the mixed micro-nanospheres are dispersed in anhydrous ethanol, the pH is adjusted to 4, methyltrimethoxysilane is added, and after ultrasonic dispersion, epoxy resin and curing agent are added, and the mixture is stirred to obtain a mixed solution, wherein the mass ratio of the mixed micro-nanospheres, methyltrimethoxysilane, epoxy resin and curing agent is 1:1-2:6-7:2-2.5; The nanocellulose aerogel is immersed in the mixed solution, allowed to stand for 1-2 hours, and dried at 80-100° C. for 1-2 hours.
[0010] By adopting the above technical scheme, strong hydrogen bonds exist between the fiber networks in the nanocellulose, so that the interaction force between the fibers is greater than the interaction force between water and the fibers, so that the whiskers aggregate to form a lamellar structure. Therefore, the nanocellulose aerogel presents a three-dimensional network structure with a small pore diameter. The air molecules are confined in pores smaller than their average free paths, which reduces the thermal conductivity and has a good thermal insulation effect. In addition, the nanocellulose aerogel is a polymer formed by cross-linking of organic polymer chains. The internal skeleton is elastic and can be deformed and compressed within a certain range, so that the elastic deformation is enhanced. Lignin microspheres and lignin nanospheres are used to construct a super hydrophobic coating on the surface of the nanocellulose aerogel, and methyltrimethoxysilane is used to undergo a hydrolysis reaction under acidic conditions to generate silanol. The silanol generates a stable polysiloxane through a self-polymerization reaction, which undergoes a cross-linking reaction with the hydroxyl groups on the surface of the lignin nanospheres and lignin microspheres to form a covalent silane layer, thereby reducing the hydroxyl groups on the surface of the lignin microspheres and lignin nanospheres, and the hydrophobic group methyl The epoxy resin has good fluidity in ethanol, and it settles on the surface of the nanocellulose aerogel earlier than the lignin nanospheres, and fills in the gaps of the accumulated lignin microspheres, making the entire micron-scale structure more solid. As the lignin nanospheres settle, a part of them is wrapped in the epoxy resin layer, and the other part enters the cavity of the lignin microspheres, providing nano-scale roughness for the coating, thereby constructing a micro-nano hierarchical structure on the surface of the nanocellulose aerogel to form a super-hydrophobic coating. Moreover, the micro-nano hierarchical structure has strong wear resistance under the strong adhesion of the epoxy resin, and can maintain good hydrophobic properties even if its surface is damaged.
[0011] Optionally, the aramid fiber is pretreated as follows: after the aramid fiber is treated with plasma, a silica sol solution containing methyltriethoxysilane is sprayed on the surface, aged for 1-2 days, immersed in anhydrous ethanol, aged at 50-60°C for 70-72h, and then supercritically dried with ethanol. The mass ratio of the aramid fiber to the silica sol solution is 1:0.1-0.3.
[0012] By adopting the above technical scheme, in order to improve the compatibility of aramid fiber with materials such as EVA resin, the aramid fiber is subjected to plasma treatment, the surface of the aramid fiber is etched, the roughness of the surface of the aramid fiber is increased, and the interface bonding ability between the aramid fiber and the silica sol liquid is improved. After supercritical drying, aramid fiber reinforced silica aerogel is obtained. The silica aerogel with low thermal conductivity fills a large number of micron- and millimeter-level holes in the aramid fiber, reducing the thermal bridge effect caused by the contact between the fibers, reducing the thermal conductivity of the aramid fiber, and the aerogel The nano-scale pore size of the gel is generally smaller than the mean free path of air molecules, the collision probability between gas molecules is reduced, and the gas heat conduction is reduced; moreover, in a low-temperature environment, the aramid fiber reinforced silica aerogel has a stable structure, no large deformation, good overall flexibility, and no large volume shrinkage, so it has good low-temperature resistance. The addition of methyltriethoxysilane can effectively improve the hydrophobic effect of the silica and aramid fiber composite aerogel, and improve the dispersion and compatibility of aramid fiber in the sole material, thereby further improving the mechanical properties of the sole material such as tensile strength.
[0013] Optionally, the silica sol solution comprises silica sol, methyltriethoxysilane, cerium dioxide and multi-walled carbon nanotubes, and the mass ratio of silica sol, methyltriethoxysilane, cerium dioxide and multi-walled carbon nanotubes is 10:0.3-0.5:0.1-0.2:0.1-0.2.
[0014] By adopting the above technical solution, multi-walled carbon nanotubes have good light-heat conversion ability due to their hydrophobic graphite-like surface structure, which can convert light energy into heat energy to increase the heat of the feet. Cerium dioxide has high chemical stability and thermal stability, and under the action of methyltriethoxysilane, multi-walled carbon nanotubes and cerium dioxide have excellent hydrophobic properties, and the bonding force of silica sol can firmly load multi-walled carbon nanotubes and cerium dioxide on the surface of aramid fibers. Nano-scale cerium dioxide and multi-walled carbon nanotubes are combined with the rough structure on the aramid fibers to form a dual-size micro-nano structure, which improves The hydrophobicity of aramid fiber is improved. When only one kind of cerium dioxide is added, the structure is relatively simple and the roughness is relatively small. Therefore, the superior hydrophobicity and the photocatalysis of nano-cerium dioxide and the photothermal conversion of multi-walled carbon nanotubes can reduce the reflectivity of visible light, improve the photothermal conversion capacity of the coating, reduce the adhesion of ice, and increase the thermal insulation effect of the sole in low temperature areas; most of the cerium dioxide particles wrapped by multi-walled carbon nanotubes are embedded in the pore structure, and the structure is more stable under the action of silica sol, which makes the particles not easy to fall off during friction, and at the same time increases the wear resistance of the sole material.
[0015] Optionally, the inorganic filler includes coal gangue powder and graphene in a mass ratio of 1:0.3-0.5.
[0016] By adopting the above technical solution, graphene has a planar hexagonal lattice structure and has a hybrid SP 2 bond, it shows a single π orbital and 3 σ bonds perpendicular to the plane. The strong in-plane σ bonds serve as a hexagonal rigid skeleton structure, while the out-of-plane π bonds control the interaction between different graphene sheets. These unique structures and special features give graphene excellent mechanical and thermal properties, which can significantly improve the tensile strength and compressive strength of the sole material, make the sole more wear-resistant, extend the service life, and improve the anti-static effect, reduce dust and sliding adsorbed by static electricity, achieve better grip, improve anti-slip properties, and graphene has good flexibility, which can maintain the strength of the sole material while increasing elasticity and comfort, improving foot support and cushioning effects; coal gangue powder, as a commonly used reinforcing filler, can form aggregates in the foamed sole material, which has the advantages of high dispersibility, light weight, good chemical stability, high temperature resistance, etc., and can significantly improve wear resistance, hardness, tensile strength and tear strength in the sole material.
[0017] Optionally, the filler is prepared as follows: Add the coal gangue powder to the silane coupling agent KH570 solution, heat to 55-60°C, stir for 3-4 hours, wash, centrifuge and dry to obtain modified coal gangue powder; The graphene is added to the tannic acid solution, ultrasonicated for 30-40 minutes, the modified coal gangue powder is added, stirred evenly, centrifuged, and vacuum dried to obtain a blend; The blend is added into the silicone resin emulsion, stirred evenly, dried and crushed to obtain the filler, and the mass ratio of the blend to the silicone resin emulsion is 1:0.08-0.12.
[0018] There are a large number of hydroxyl groups on the surface of coal gangue powder and graphene, and the specific surface area is large, which makes the surface polarity higher and the intermolecular force strong, and it is very easy to have serious nano-agglomeration, resulting in poor dispersion and compatibility of graphene and filler in the foamed sole material. By adopting the above technical scheme, the gangue powder is modified by using the silane coupling agent KH570. After KH570 is hydrolyzed, it undergoes a condensation reaction with the hydroxyl groups on the surface of the gangue powder to form chemical bonds, thereby preventing the agglomeration of the gangue powder. The phenolic hydroxyl groups on the tannic acid combine with the end groups of the graphene to form hydrogen bonds, thereby playing the role of functionalized graphene. The silane-modified gangue powder and the functionalized graphene are blended to undergo a Michael addition reaction. The functionalized graphene and the modified gangue powder are interspersed and combined with each other, thereby effectively inhibiting the stacking of graphene sheets and the agglomeration of the gangue powder, thereby improving the dispersibility of the blend in the silicone resin emulsion, coating the silicone resin on the surface of the blend, thereby improving the dispersibility of the blend, thereby enhancing the intermolecular force of the sole material, and exhibiting better tensile properties on the surface. The blend can undergo a cross-linking reaction in the foamed sole to form a dense cross-linking network, thereby improving the mechanical strength of the reinforced sole material. The silicone resin can coat and solidify the surface of the blend to form a hydrophobic coating. Because the silicone resin itself has the characteristics of low surface energy, the coating surface is not easily wetted by water molecules, thereby increasing the dispersibility and compatibility between the filler and the matrix components such as EVA resin, making the filler more evenly distributed in the foamed sole material, reducing the effect of agglomeration on the mechanical strength of the sole material, and it is a thermosetting resin. The coating formed on the surface of the blend will not melt during foaming. The silicone resin is composed of silicon atoms and organic groups connected by silicon-oxygen bonds. This special structure gives it excellent wear resistance and anti- Oxidizability, high and low temperature resistance and water resistance can enhance the effect of fillers on the wear resistance of foam sole materials. In addition, silicone resin is a material with low thermal conductivity, which can effectively reduce the efficiency of heat transfer, reduce the transfer of heat from high temperature areas to low temperature areas, and maintain the stability of the temperature inside the shoes. Moreover, silicone resin is not easy to age, has good corrosion resistance and environmental protection, and will not cause pollution to the environment. It can also increase the flexibility of EVA molecular chains, making EVA more prone to elastic deformation when subjected to external forces, and quickly return to its original state after the external force is removed, thereby improving the resilience of the foam sole material.
[0019] Optionally, the EVA resin includes a type I EVA resin with a VA content of 28-40% and a type II EVA resin with a VA content of 8-12% in a mass ratio of 1:0.5-0.7.
[0020] By adopting the above technical scheme, the VA content in Type I EVA resin is higher, and it has better resilience, flexibility and impact resistance, which can improve the low-temperature brittleness resistance of the sole material. The VA content in Type II EVA resin is lower, and it has higher rigidity, thereby improving the wear resistance of the sole material.
[0021] Optionally, the cross-linking agent is at least one of dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxide and sulfur.
[0022] By adopting the above technical solution, the cross-linking agent can form chemical bonds between molecular chains, thereby transforming the linear molecular structure into a three-dimensional network structure, improving the strength, heat resistance and wear resistance of the material.
[0023] Optionally, the foaming agent is azodicarbonamide.
[0024] In a second aspect, the present application provides a method for preparing a lightweight sole material, using the following technical solution: A method for preparing a lightweight sole material comprises the following steps: The EVA resin, polyamide elastomer and thermoplastic polyurethane are mixed and kneaded for 12-20 minutes to obtain a premix, and the hydrophobically modified nanocellulose aerogel, aramid fiber and inorganic filler are added, kneaded and discharged to obtain an intermediate material; The intermediate material is mixed with a foaming agent, a cross-linking agent, zinc oxide and stearic acid, and kneaded to obtain a foamed sheet; The foam sheet is cut into a sole shape and foamed to obtain a lightweight sole material.
[0025] By adopting the above technical solution, the EVA resin is firstly kneaded with the polyamide elastomer and the thermoplastic polyurethane to increase the mixing uniformity between the three raw materials and improve the foaming performance.
[0026] In summary, this application has the following beneficial effects: 1. Since the present application adopts EVA resin and polyamide elastomer, thermoplastic polyurethane, hydrophobically modified nanocellulose aerogel and aramid fiber and other raw materials to prepare the sole material, the tensile strength of the sole material at room temperature and low temperature can be effectively improved, so that the sole material is not easy to become brittle and hard at low temperature, thereby improving the comfort and flexibility of the sole in low temperature environment.
[0027] 2. In the present application, lignin microspheres and lignin nanospheres treated with methyltrimethoxysilane for hydrophobic treatment are preferably used. After mixing with epoxy resin, the nanocellulose aerogel is subjected to natural sedimentation treatment. The lignin microspheres with larger particle size will first settle on the surface of the nanocellulose aerogel, and build a micron-scale protrusion structure by stacking each other. Then the epoxy resin settles to make the micron-scale structure more solid. Finally, the lignin nanospheres settle, and part of them are wrapped in the epoxy resin layer, and part of them enter the cavity of the lignin microspheres, thereby forming a hierarchical structure of nanoscale cores and micrometers, and obtaining a super-hydrophobic coating with higher stability, thereby improving the hydrophobicity of the nanocellulose aerogel, increasing its dispersibility in the sole material, and at the same time further increasing the wear resistance of the sole.
[0028] 3. In this application, silica sol containing methyltriethoxysilane is preferentially used to treat aramid fibers, which reduces the thermal conductivity of aramid fibers and improves the thermal insulation effect of the sole material. At the same time, cerium dioxide and multi-walled carbon nanotubes are added to increase the sole's conversion of light and heat, and increase the thermal insulation capacity of the sole material in areas with lower temperatures.
[0029] 4. In this application, coal gangue powder and graphene are preferentially used as fillers, and the coal gangue powder is modified by KH570, and the graphene is functionalized by tannic acid, and a Michael addition reaction occurs between the two, thereby improving the dispersibility of the coal gangue powder and graphene in the silicone resin emulsion, and coating the surface of the coal gangue powder and graphene with thermosetting silicone resin to improve the dispersibility of the filler in the sole, and the stability of the filler can still be maintained during foaming, thereby improving the mechanical strength and wear resistance of the sole material. DETAILED DESCRIPTION
[0030] The following examples further illustrate the present application in detail.
[0031] Preparation example of lignin nanospheres and lignin microspheres Preparation Example I of lignin nanospheres: 40 mg of enzymatically hydrolyzed lignin was added to 2 mL of a binary solvent containing γ-pentylpropyl ester and ultrapure water in a volume ratio of 9:1 to prepare a lignin solution with a concentration of 20 mg / ml, which was quickly injected into 16 ml of ultrapure water at a temperature of 25°C and maintained for 10 min. The obtained lignin nanosphere suspension was transferred to a dialysis bag with a molecular weight cutoff of 1000, immersed in ultrapure water to remove excess γ-pentylpropyl ester, added to a 100-mL autoclave lined with Teflon, heated at 160°C for 12 h, and freeze-dried to obtain a solid powder of lignin nanospheres.
[0032] Preparation Example II of lignin microspheres: 40 mg of enzymatically hydrolyzed lignin was added to 2 ml of a binary solvent containing γ-pentyl propyl ester and ultrapure water in a volume ratio of 1:4 to prepare a lignin solution with a concentration of 20 mg / ml, which was quickly injected into 16 ml of ultrapure water at a temperature of 50°C and maintained for 20 min, centrifuged at 2000 rpm, added to a 100-mL autoclave lined with Teflon, heated at 160°C for 12 h, and freeze-dried to obtain lignin microsphere powder with an average particle size of 1 μm.
[0033] Preparation Examples 1-5 of Hydrophobically Modified Nanocellulose Aerogels Preparation Example 1: 1.5 g of nanocellulose was dispersed in deionized water to prepare a suspension with a concentration of 1.5 wt%, the pH was adjusted to 4 with 0.1 mol / l dilute hydrochloric acid, methyltrimethoxysilane was added, and the mixture was stirred at a speed of 1000 r / min for 2 h. After freezing with liquid nitrogen (-196°C) for 30 min, the mixture was freeze-dried in a freeze dryer at a temperature of -40°C and a vacuum degree of less than 15 Pa for 24 h to obtain a hydrophobically modified nanocellulose aerogel, wherein the mass ratio of nanocellulose to methyltrimethoxysilane was 1:2.
[0034] Preparation Example 2: 1.5 g of nanocellulose was dispersed in deionized water to prepare a suspension with a concentration of 1.5 wt%, and after freezing in liquid nitrogen (-196° C.) for 30 min, freeze-dried in a freeze dryer at a temperature of -40° C. and a vacuum degree of less than 15 Pa for 24 h to obtain nanocellulose aerogel; 1 g of lignin microspheres and 0.5 g of lignin micro-nanospheres were mixed to form a mixed micro-nanosphere, and the mixed micro-nanospheres were dispersed in 1.3 L of anhydrous ethanol, and the pH was adjusted to 4 with 0.1 mol / l of dilute hydrochloric acid, and 3 g of methyltrimethoxysilane was added. After ultrasonic dispersion, 9 g of epoxy resin and 3 g of curing agent were added, and the mixture was stirred evenly to obtain a mixed solution, wherein the mass ratio of the mixed micro-nanospheres, methyltrimethoxysilane, epoxy resin and curing agent was 1:2:6:2, the lignin nanospheres were prepared according to Preparation Example I, the lignin microspheres were prepared according to Preparation Example II, the epoxy resin was bisphenol A type, model E-51, and the curing agent was ethylenediamine; The nanocellulose aerogel was immersed in the mixed solution, left to stand for 2 h, and dried at 80 °C for 2 h.
[0035] Preparation Example 3: 1 g of nanocellulose was dispersed in deionized water to prepare a suspension with a concentration of 1 wt%, and after freezing in liquid nitrogen (-196° C.) for 30 min, freeze-dried in a freeze dryer at a temperature of -40° C. and a vacuum degree of less than 15 Pa for 24 h to obtain nanocellulose aerogel; 1 g of lignin microspheres and 1 g of lignin micro-nanospheres were mixed to form a mixed micro-nanosphere, and the mixed micro-nanospheres were dispersed in 1.3 L of anhydrous ethanol, and the pH was adjusted to 4 with 0.1 mol / l of dilute hydrochloric acid, and 2 g of methyltrimethoxysilane was added. After ultrasonic dispersion, 14 g of epoxy resin and 5 g of curing agent were added, and the mixture was stirred evenly to obtain a mixed solution, wherein the mass ratio of the mixed micro-nanospheres, methyltrimethoxysilane, epoxy resin and curing agent was 1:1:7:2.5, the lignin nanospheres were prepared according to Preparation Example I, the lignin microspheres were prepared according to Preparation Example II, the epoxy resin was bisphenol A type, model E-51, and the curing agent was ethylenediamine; The nanocellulose aerogel was immersed in the mixed solution, left to stand for 1 h, and dried at 100 °C for 1 h.
[0036] Preparation Example 4: The difference from Preparation Example 2 is that no lignin nanospheres are added.
[0037] Preparation Example 5: The difference from Preparation Example 2 is that no lignin microspheres are added. Example
[0038] Embodiment 1: A lightweight sole material, the raw material dosage is as shown in Table 1, the EVA resin is obtained by mixing type I EVA resin with a VA content of 40% and type II EVA resin with a VA content of 8% in a mass ratio of 1:0.7, the type I EVA resin is selected from Mitsui Chemicals, model 40W, and the type II EVA resin is selected from Taiwan Polymerization, model UE508; the polyamide elastomer is selected from Mitsubishi of Japan, brand 3010GN30; the thermoplastic polyurethane is selected from BASF of Germany, brand 1260DU; the foaming agent is azodicarbonamide; the cross-linking agent is diisopropyl peroxide; the inorganic filler is coal gangue powder, with a particle size of 10 μm; the aramid fiber has a length of 3 mm, is selected from Jiangxi Shuobang, model FLXW06; the hydrophobically modified nanocellulose aerogel is prepared by Preparation Example 1.
[0039] The method for preparing the above-mentioned lightweight sole material comprises the following steps: EVA resin, polyamide elastomer and thermoplastic polyurethane are mixed, kneaded at 145°C for 20 minutes to obtain a premix, and hydrophobically modified nanocellulose aerogel, aramid fiber and inorganic filler are added, first kneaded at 102°C, turned over once after 3 minutes, turned over twice when the temperature is raised to 108°C, turned over three times when the temperature is raised to 116°C, turned over four times when the temperature is raised to 125°C, turned over five times when the temperature is raised to 130°C, kneaded for another 2 minutes, and then discharged, and placed at room temperature for more than 24 hours to obtain an intermediate material; The intermediate material was mixed with a foaming agent, a cross-linking agent, zinc oxide and stearic acid, kneaded at 140°C for 5 minutes, thinned twice, and sheeted to obtain a 2mm thick foamed sheet; The foamed sheet is cut into a sole shape, and foamed at 160° C. and a molding pressure of 10 MPa for 300 seconds to obtain a lightweight sole material.
[0040] Table 1 Raw material dosage of lightweight sole material in Examples 1-3 Example 2: A lightweight sole material, which differs from Example 1 in that the amounts of raw materials are as shown in Table 1, and the EVA resin is obtained by mixing a type I EVA resin with a VA content of 28% and a type II EVA resin with a VA content of 12% in a mass ratio of 1:0.5, the type I EVA resin is selected from DuPont of the United States, model 3175, and the type II EVA resin is selected from DuPont of the United States, model 670.
[0041] Example 3: A lightweight sole material, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.
[0042] Embodiment 4: A lightweight sole material, which is different from Embodiment 1 in that the EVA resin is type II EVA resin.
[0043] Embodiment 5: A lightweight sole material, which is different from Embodiment 1 in that the EVA resin is type I EVA resin.
[0044] Example 6: A lightweight sole material, which is different from Example 1 in that the hydrophobically modified nanocellulose aerogel is made from Preparation Example 2.
[0045] Example 7: A lightweight sole material, which is different from Example 1 in that the hydrophobically modified nanocellulose aerogel is made from Preparation Example 3.
[0046] Example 8: A lightweight sole material, which is different from Example 6 in that the hydrophobically modified nanocellulose aerogel is made from Preparation Example 4.
[0047] Example 9: A lightweight sole material, which is different from Example 6 in that the hydrophobically modified nanocellulose aerogel is made from Preparation Example 5.
[0048] Embodiment 10: A lightweight sole material, which differs from Embodiment 6 in that the aramid fiber is subjected to the following pretreatment: the aramid fiber is plasma treated for 120 seconds at a pressure of 60Pa and a power of 150W, and then a silica sol solution containing methyltriethoxysilane is sprayed on the surface. After aging for 1 day, the fiber is immersed in anhydrous ethanol and aged at 50°C for 72 hours, and then supercritically dried with ethanol. The mass ratio of the aramid fiber to the silica sol solution is 1:0.3, and the silica sol solution is prepared by mixing silica sol, methyltriethoxysilane, cerium dioxide and multi-walled carbon nanotubes in a mass ratio of 10:0.5:0.2:0.2. The silica sol is selected from Xuancheng Jingrui New Materials, model VK-S01N, the cerium dioxide particle size is 20nm, and the outer diameter of the multi-walled carbon nanotubes is 20nm.
[0049] Embodiment 11: A lightweight sole material, which differs from Embodiment 6 in that the aramid fiber is subjected to the following pretreatment: the aramid fiber is plasma treated for 120 seconds at a pressure of 60Pa and a power of 150W, and then a silica sol solution containing methyltriethoxysilane is sprayed on the surface. After aging for 2 days, the fiber is immersed in anhydrous ethanol and aged at 60°C for 70 hours, and then supercritically dried with ethanol. The mass ratio of the aramid fiber to the silica sol solution is 1:0.1, and the silica sol solution is prepared by mixing silica sol, methyltriethoxysilane, cerium dioxide and multi-walled carbon nanotubes in a mass ratio of 10:0.3:0.1:0.1. The silica sol is selected from Xuancheng Jingrui New Materials, model VK-S01N, the cerium dioxide particle size is 20nm, and the outer diameter of the multi-walled carbon nanotubes is 20nm.
[0050] Example 12: A lightweight sole material, which is different from Example 10 in that multi-walled carbon nanotubes are not added to the silica sol solution.
[0051] Example 13: A lightweight sole material, which is different from Example 10 in that multi-walled carbon nanotubes and cerium dioxide are not added.
[0052] Embodiment 14: A lightweight sole material, which is different from Embodiment 10 in that the filler comprises coal gangue powder and graphene in a mass ratio of 1:0.5, and the filler is made by the following method: Silane coupling agent KH570 is added into a mixed solvent containing deionized water and ethanol in a volume ratio of 1:10 to prepare a silane coupling agent KH570 solution with a concentration of 10wt%, 20g of coal gangue powder is added, the temperature is raised to 55°C, and the mixture is stirred at a speed of 5000r / min for 3h, then washed with ethanol for 3 times, centrifuged at a speed of 8000rpm for 6min, and dried at 60°C for 48h to obtain modified coal gangue powder; 10 g of graphene was added to a tannic acid solution with a concentration of 0.03 g / ml, and ultrasonicated for 30 min to obtain functionalized graphene, and modified coal gangue powder was added, stirred evenly, centrifuged, and vacuum dried at 60° C. to obtain a blend; The blend is added to the silicone resin emulsion, stirred evenly, dried and crushed to obtain the filler, the mass ratio of the blend to the silicone resin emulsion is 1:0.12, the silicone resin emulsion is a water-based silicone resin emulsion selected from Wacker of Germany, model MP50E.
[0053] Embodiment 15: A lightweight sole material, which is different from Embodiment 10 in that the filler comprises coal gangue powder and graphene in a mass ratio of 1:0.3, and the filler is made by the following method: The silane coupling agent KH570 is added into a mixed solvent containing deionized water and ethanol in a volume ratio of 1:10 to prepare a silane coupling agent KH570 solution with a concentration of 10wt%, 23g of coal gangue powder is added, the temperature is raised to 60°C, and the mixture is stirred at a speed of 5000r / min for 4h, then washed with ethanol for 3 times, centrifuged at a speed of 8000rpm for 6min, and dried at 60°C for 48h to obtain modified coal gangue powder; 7 g of graphene was added to a tannic acid solution with a concentration of 0.03 g / ml, and ultrasonicated for 40 min to obtain functionalized graphene, and modified coal gangue powder was added, stirred evenly, centrifuged, and vacuum dried at 60° C. to obtain a blend; The blend is added to the silicone resin emulsion, stirred evenly, dried and crushed to obtain the filler, the mass ratio of the blend to the silicone resin emulsion is 1:0.08, the silicone resin emulsion is a water-based silicone resin emulsion selected from Wacker of Germany, model MP50E.
[0054] Example 16: A lightweight sole material, which is different from Example 14 in that the coal gangue has not been modified with a silane coupling agent and the graphene has not been pretreated with tannic acid.
[0055] Example 17: A lightweight sole material, which is different from Example 14 in that silicone resin emulsion is not used and the blend is used as filler.
[0056] Comparative Example Comparative Example 1: A lightweight sole material, which is different from Example 1 in that no polyamide elastomer is added.
[0057] Comparative Example 2: A lightweight sole material, which is different from Example 1 in that thermoplastic polyurethane is not added.
[0058] Comparative Example 3: A lightweight sole material, which differs from Example 1 in that no hydrophobically modified nanocellulose aerogel is added.
[0059] Comparative Example 4: A lightweight sole material, which differs from Example 1 in that aramid fiber is not added.
[0060] Performance testing The lightweight sole material was prepared according to the methods in the examples and comparative examples, and the performance was tested according to the following method. The test results are recorded in Table 2.
[0061] 1. Density: Test in accordance with GB / T6343-1995 "Determination of apparent (volume) density of rigid foam and rubber".
[0062] 2. Tensile strength: The test was carried out in accordance with GB / T6344-1996 "Determination of tensile strength and elongation at break of soft foam polymer materials", and the tensile speed was 500 mm / min.
[0063] 3. Rebound rate: The test is carried out in accordance with GB / T6670-2008 "Determination of rebound properties of soft foam polymer materials by falling ball method", the sample specifications are 100mm×100mm×50mm, and the falling height of the steel ball is 460mm.
[0064] 4. Akron wear: The test is carried out in accordance with GB / T1689-2014 "Determination of wear resistance of vulcanized rubber (using Akron abrasion tester)", the sample specification length (mm) = (wheel rubber diameter + 2 × sample thickness) × 3.14 (D + 2h) πmm, the width is (12.7 ± 0.2) mm, and the thickness is (3.2 ± 0.2) mm.
[0065] 5. Low temperature resistance: The sole foam material is cut and bonded into a cube, a temperature sensor is placed inside the cube, and then the cube is placed in a sealed bag and heated in a 37°C constant temperature water bath. When the temperature inside the cube reaches 37°C, the cube is quickly taken out and placed in a -50°C low-temperature refrigerator for testing. The digital thermometer will record the temperature change inside the cube. The test is terminated when the temperature drops to 0°C. The time from 37°C to 0°C is defined as the low temperature resistance time. The longer the time, the better the low temperature resistance and heat insulation performance of the sole material. The sample of each embodiment or comparative example is measured 5 times and the average value is taken.
[0066] Table 2 Performance test of lightweight sole materials Combining Examples 1-3 and the data in Table 2, it can be seen that the foamed sole material is prepared by blending raw materials such as polyamide elastomer, thermoplastic polyurethane, hydrophobically modified nanocellulose aerogel, aramid fiber and EVA resin, and the hydrophobically modified nanocellulose aerogel is prepared by modification with methyltrimethoxysilane. The obtained sole material has ultra-low density, good resilience, light weight, comfort, high tensile strength, good flexibility, high toughness at low temperatures, excellent resistance to low-temperature brittleness, good thermal insulation effect in low-temperature environments, and reduces heat loss from the feet.
[0067] In Example 4 and Example 5, separate Type II EVA resin and Type I EVA resin are used respectively. The data in Table 2 show that the sole material prepared in Example 4 has better wear resistance, but the tensile strength is reduced, and the low temperature resistance is reduced, and the rebound rate is reduced. The sole material prepared in Example 5 has better low temperature resistance, but weakened wear resistance, indicating that the use of two EVA resins with different VA contents can produce a better synergistic effect, thereby improving the toughness, low temperature toughness and wear resistance of the sole material.
[0068] Compared with Example 1, Example 6 and Example 7 respectively use the hydrophobically modified nanocellulose aerogel prepared in Preparation Example 2 and Preparation Example 3. The mechanical strength of the sole materials prepared in Example 6 and Example 7 is increased, and the Akron wear is slightly improved, the low temperature resistance time is increased, and the heat insulation and thermal insulation capabilities are enhanced.
[0069] Compared with Example 6, Examples 8 and 9 used the hydrophobically modified nanocellulose aerogel prepared in Preparation Examples 4 and 5, respectively. Compared with Preparation Example 1, Preparation Examples 4 and 5 did not add lignin nanospheres and lignin microspheres, respectively. The sole materials prepared in Examples 8 and 9 had reduced tensile strength, increased Akron wear, weakened wear resistance, and weakened thermal insulation capabilities.
[0070] Compared with Example 6, Examples 10 and 11 not only use the hydrophobically modified nanocellulose aerogel prepared in Preparation Example 2, but also use silica sol solution to pretreat the aramid fiber. From the data in Table 2, it can be seen that the tensile strength of the sole materials prepared in Examples 10 and 11 is increased, the low temperature resistance is improved, the wear resistance is enhanced, the low temperature resistance time is prolonged, and the low temperature resistance effect is increased.
[0071] Compared with Example 10, Example 12 does not add multi-walled carbon nanotubes. Compared with Example 10, Example 13 does not add multi-walled carbon nanotubes and cerium dioxide. The data in Table 2 show that the tensile strength of the sole materials prepared in Examples 12 and 13 is slightly reduced, and the wear resistance is significantly weakened.
[0072] Compared with Example 10, Example 14 and Example 15 use graphene and coal gangue powder to prepare fillers. Table 2 shows that the wear resistance of the sole materials prepared in Example 14 and Example 15 is significantly increased, and the rebound rate is increased.
[0073] In Example 16, compared with Example 14, the gangue powder and graphene were not processed, and the wear resistance and tensile strength of the sole material decreased, indicating that the gangue powder and graphene may agglomerate and affect the dispersibility.
[0074] Compared with Example 14, Example 17 does not add silicone emulsion to treat the blend. It can be seen from the data in Table 2 that the wear resistance of the sole material made in Example 17 is reduced.
[0075] Compared with Example 1, Comparative Examples 1 and 2 do not add polyamide elastomer and thermoplastic polyurethane. As shown in Table 2, the density of the sole materials prepared in Comparative Examples 1 and 2 is increased, the tensile strength and low-temperature toughness are reduced, and the wear resistance and resilience are affected to a certain extent.
[0076] In Comparative Example 3, no hydrophobically modified nanocellulose aerogel was added. Table 2 shows that, compared with Example 1, the tensile properties of the sole material prepared in Comparative Example 3 were reduced, the low temperature resistance was weakened, and the low temperature resistance and warmth retention effect were worse.
[0077] Compared with Example 1, Comparative Example 4 does not add aramid fiber. It can be seen that the mechanical properties of the sole material made in Comparative Example 4 are deteriorated, the toughness is reduced, and the wear resistance is weakened.
[0078] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A lightweight sole material, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of EVA resin, 4-6 parts of polyamide elastomer, 8-12 parts of thermoplastic polyurethane, 8-24 parts of hydrophobically modified nanocellulose aerogel, 3-7 parts of aramid fiber, 1-3 parts of foaming agent, 1.5-2 parts of cross-linking agent, 20-40 parts of inorganic filler, 0.5-1.5 parts of zinc oxide and 0.3-0.7 parts of stearic acid.
2. The lightweight sole material according to claim 1, characterized in that: The method for preparing the hydrophobically modified nanocellulose aerogel comprises the following steps: The nanocellulose is dispersed in deionized water to prepare a suspension with a concentration of 1-1.5 wt%, and freeze-dried to obtain a nanocellulose aerogel; The lignin microspheres and lignin micro-nanospheres are mixed in a mass ratio of 1:0.5-1, the mixed micro-nanospheres are dispersed in anhydrous ethanol, the pH is adjusted to 4, methyltrimethoxysilane is added, and after ultrasonic dispersion, epoxy resin and curing agent are added, and the mixture is stirred to obtain a mixed solution, wherein the mass ratio of the mixed micro-nanospheres, methyltrimethoxysilane, epoxy resin and curing agent is 1:1-2:6-7:2-2.5; The nanocellulose aerogel is immersed in the mixed solution, allowed to stand for 1-2 hours, and dried at 80-100° C. for 1-2 hours.
3. The lightweight sole material according to claim 1, characterized in that: The aramid fiber is pretreated as follows: after the aramid fiber is treated with plasma, a silica sol solution containing methyltriethoxysilane is sprayed on the surface, aged for 1-2 days, immersed in anhydrous ethanol, aged at 50-60° C. for 70-72 hours, and then supercritically dried with ethanol, and the mass ratio of the aramid fiber to the silica sol solution is 1:0.1-0.
3.
4. The lightweight sole material according to claim 3, characterized in that: The silica sol liquid comprises silica sol, methyltriethoxysilane, cerium dioxide and multi-walled carbon nanotubes, and the mass ratio of silica sol, methyltriethoxysilane, cerium dioxide and multi-walled carbon nanotubes is 10:0.3-0.5:0.1-0.2:0.1-0.
2.
5. The lightweight sole material according to claim 1, characterized in that: The inorganic filler comprises coal gangue powder and graphene in a mass ratio of 1:0.3-0.
5.
6. The lightweight sole material according to claim 1, characterized in that: The preparation method of the filler is as follows: Add the coal gangue powder to the silane coupling agent KH570 solution, heat to 55-60°C, stir for 3-4 hours, wash, centrifuge and dry to obtain modified coal gangue powder; The graphene is added to the tannic acid solution, ultrasonicated for 30-40 minutes, the modified coal gangue powder is added, stirred evenly, centrifuged, and vacuum dried to obtain a blend; The blend is added into the silicone resin emulsion, stirred evenly, dried and crushed to obtain the filler, and the mass ratio of the blend to the silicone resin emulsion is 1:0.08-0.
12.
7. The lightweight sole material according to claim 1, characterized in that: The EVA resin includes a type I EVA resin having a VA content of 28-40% and a type II EVA resin having a VA content of 8-12% in a mass ratio of 1:0.5-0.
7.
8. The lightweight sole material according to claim 1, characterized in that: The cross-linking agent is at least one of dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxide and sulfur.
9. The lightweight sole material according to claim 1, characterized in that: The foaming agent is azodicarbonamide.
10. The method for preparing the lightweight sole material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The EVA resin, polyamide elastomer and thermoplastic polyurethane are mixed and kneaded for 12-20 minutes to obtain a premix, and the hydrophobically modified nanocellulose aerogel, aramid fiber and inorganic filler are added, kneaded and discharged to obtain an intermediate material; The intermediate material is mixed with a foaming agent, a cross-linking agent, zinc oxide and stearic acid, and kneaded to obtain a foamed sheet; The foam sheet is cut into a sole shape and foamed to obtain a lightweight sole material.
Citation Information
Cited By
Shock-absorbing damping rubber EVA (Ethylene Vinyl Acetate) foaming material and preparation method thereof
CN120757910A
Shock-absorbing damping rubber EVA foaming material and preparation method thereof
CN120757910B